Development Support Learning Media Based on Android in Subject Operation System - Rafiqa Rizalita; Fahmi Rizal (Universitas Negeri Padang, 2020)
This media designed to increase motivation and creativity of students so that students can understand the overall material provided in the subject operation system. This research used the development metode was 4D (Four D), while the 4D development procedure those were: define, design, develop, and Disseminate. Data type was primary data where the data provided by the media experts, lecturers and students. Data analysis technique used was descriptive data analysis technique those were describe the validity, practicality and effectiveness of using support learning media. Results obtained from this development research as follows; (1) The validity of support learning media expressed very valid on the media design with a value of validity was 0.828, while the materi of media was valid for a value was 0.703, (2) the practicalities of support learning media based the response of teachers after going through practical trials with a total value was 84.66%, while the practicalities of support learning media based on student response after going through the otherwise very practical trials with a total value of 87.96%.